1989
DOI: 10.1111/j.2042-3306.1989.tb02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Laryngotracheal lesions following routine orotracheal intubation in the horse

Abstract: Summary Sequelae of routine orotracheal intubation under clinical conditions were characterised in 38 healthy horses presented at three veterinary medical teaching hospitals. Four of these were necropsied and their tissues studied histologically. To minimise variation, 30 mm id cuffed silicone endotracheal tubes or Cole cuffless tubes were used in all patients. Fibreoptic endoscopic examination of upper respiratory and tracheal areas was accomplished pre‐intubation, immediately post extubation and after 24 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…Though the number of attempts did not differ between SGAD and ETT, our results show that even one to two attempts with ETT resulted in measurable trauma to the tracheal tissues. Similar findings have been reported in horses and our findings are consistent with those of Phaneuf et al, where histologic changes were reported after a single intubation event (the number of attempts was not reported) using both cuffed and uncuffed endotracheal tubes (7, 23). Since animals were euthanized at the end of our study, the consequences of the histologic changes are unknown; however, morbidity and mortality have been reported following apparently uneventful blind orotracheal intubations (7, 24).…”
Section: Discussionsupporting
confidence: 93%
“…Though the number of attempts did not differ between SGAD and ETT, our results show that even one to two attempts with ETT resulted in measurable trauma to the tracheal tissues. Similar findings have been reported in horses and our findings are consistent with those of Phaneuf et al, where histologic changes were reported after a single intubation event (the number of attempts was not reported) using both cuffed and uncuffed endotracheal tubes (7, 23). Since animals were euthanized at the end of our study, the consequences of the histologic changes are unknown; however, morbidity and mortality have been reported following apparently uneventful blind orotracheal intubations (7, 24).…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to cigarette smoke results in hypersecretion in the airways [13]. Orotracheal intubation-induced injury and other types of mechanical damage to the airway epithelium also result in mucus hypersecretion [14,15,16]. Neutrophils and their products are implicated in cystic fibrosis [10], COPD [11], and acute severe asthma [17].…”
Section: Stimuli For Mucin Synthesis: Role Of the Epidermal Growth Famentioning
confidence: 99%
“…The authors of those studies did not comment on goblet-cell metaplasia. However, in horses, orotracheal intubation results in mucus hypersecretion [14], and mechanical denudation of hamster airways results in secretory-cell metaplasia [15]. Lee et al [16] instilled irregular agarose plugs into rat airways to produce irritation, which also resulted in a profound increase in goblet cells.…”
Section: Stimuli For Mucin Synthesis: Role Of the Epidermal Growth Famentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly a third of these patients are at risk for the development of ventilator-associated pneumonia (VAP). Intubation causes mucous hypersecretion in animals (26) and that mechanical irritation causes upregulation of mucin production via EGFR activation (12). The presence of mucins in secretions creates an atmosphere conducive for the growth of certain bacteria, and subsequent aspiration of mucus-containing bacteria results in VAP, the leading cause of death from hospital-acquired infection.…”
mentioning
confidence: 99%